THE POTENTIAL OF MAIZE AS PHYTOREMEDIATION TOOL OF HEAVY METALS - Aliyu, H. G.; Adamu, H. M. (European Scientific Journal, ESJ, 2014)
This paper shows result obtained from analysis done on some selected heavy metals accumulated in maize planted in contaminated soil for forty two days. The soil (3kg) each was contaminated with 2g of the metals (as FeSO4, CdCO3 and Zn, Mn, Pb, and Cr powder), adapting experimental method of Abd-El Naby 2002 . The results show that essential heavy metals (Fe, Zn and Mn) at day 14 were high with values of 28.275±0.05, 18.210±0.03 and 4.815±0.11 in the experimental and Fe and Zn were high at 28 days with values of 30.21±0.02 and 16.52± 0.01, while at 42 days Fe and Mn were high with values of 33.01±0.00 and 16.88±0.01 respectively. The result for the control soil indicates that Fe, Pb and Zn reduced considerably with values of 3.650± 0.06, 2.006±0.00 and 1.113±0.00 respectively while at day 28 and 42 the same trend was observed to be as day 14. Generally, it was observed that the heavy metals accumulation by the plant in soil for both experimental and control is high in maize. The results show that maize can be used to phytoremediate these metals.